Residual pulmonary vascular obstruction computed with ventilation/perfusion single photon emission computed tomography/computed tomography to predict the risk of venous thromboembolism recurrence in patients with pulmonary embolism: protocol for a cohort study (PRONOSPECT) - Pierre–Yves Le Roux; Philippe Robin; Romain Le Pennec; Cécile Tromeur; Francis Couturaud; Julien Asselineau; Grégoire Le Gal; Pierre–Yves Salaun (Research and Practice in Thrombosis and Haemostasis)
Background: In patients with pulmonary embolism (PE), identifying predictors of recurrence is important to risk-stratify patients and tailor anticoagulation duration. After PE, a significant proportion of patients demonstrate residual pulmonary vascular obstruction (RPVO) on lung imaging. However, the exact prognostic significance of RPVO for venous thromboembolism recurrence remains unclear. Objectives: The primary objective is to assess whether RPVO on ventilation/perfusion (V/Q) single photon emission computed tomography (SPECT)/CT imaging after completion of 3 to 6 months of anticoagulation is an independent predictor of venous thromboembolism recurrence in patients with PE. Methods: The PRONOSPECT trial is a prospective multicenter cohort study. Participants are patients who experienced an objectively proven PE, provoked by a minor transient risk factor or unprovoked; who have been treated with anticoagulant therapy for 3 to 6 uninterrupted months; and for whom anticoagulation will not be prolonged. A standardized baseline patient assessment will be conducted including V/Q SPECT/CT imaging, collection of other potential predictor variables, and a functional evaluation. Anticoagulants will be withdrawn at the 3- or 6-month points from diagnosis and patients will be followed up for up to 2 years. Conclusion: The PRONOSPECT cohort study has the potential to determine whether the presence of RPVO on V/Q SPECT/CT imaging predicts the risk of recurrence in patients with PE in whom there remains a doubt on duration of anticoagulation.